Presenilin modulates EGFR signaling and cell transformation by regulating the ubiquitin ligase Fbw7 - Rocher-Ros, V; Marco, S; Mao, J-H; Gines, S; Metzger, D; Chambon, P; Balmain, A; Saura, C A (Oncogene, 2010)
The epidermal growth factor receptor (EGFR) and Notch signaling pathways have antagonistic roles during epidermal differentiation and carcinogenesis. The molecular mechanisms regulating the crosstalk between EGFR and Notch during epidermal transformation are largely unknown. We found enhanced EGFR-dependent signaling, proliferation and oncogenic transformation caused by loss of presenilins (PS), the catalytic components of γ-secretase that generates the Notch1 intracellular domain (NICD). The underlying mechanism for abnormal EGFR signaling in PS-deficient cells involves γ-secretase-independent transcriptional upregulation of the E3 ubiquitin ligase Fbw7. Fbw7α, which targets NICD for degradation, regulates positively EGFR by affecting a proteasome-dependent ubiquitination step essential for constitutive degradation and stability of EGFR. To investigate the pathological relevance of this findings in vivo , we generated a novel epidermal conditional PS-deficient (ePS cDKO) mouse by deleting both PS in keratinocytes of the basal layer of the epidermis. The ePS cDKO mice develop epidermal hyperplasia associated with enhanced expression of both EGFR and Fbw7 and reduced NICD levels in keratinocytes. These findings establish a novel role for PS on epidermal growth and transformation by reciprocally regulating the EGFR and Notch signaling pathways through Fbw7.